The corneal biomechanical changes of phacoemulsification in cataract patients: A systematic review and meta-analysis - Xinru Li; Xiaofeng Li; Lintong Tan; Hu Chen; Yuan Lai (PLoS ONE, 2025)
Purpose To evaluate the corneal biomechanical properties of phacoemulsification in the treatment of cataract patients. Methods Pertinent studies were searched in PubMed, EMBASE, Web of Science and clinicaltrials.gov., as of November 05, 2024. The reference lists of related published reviews were included as well. This meta-analysis was performed with Stata Software and Review Manager, we used mean difference (MD) to evaluate the statistical consequence, using I2 statistic to assess the heterogeneity. Subgroup analysis were performed under the occurrences of high heterogeneity. We used eleven items to describe the characteristics of included studies, publication bias was performed with Egger’s test. The quality assessment were evaluated with 3 items by Newcastle-Ottawa Scale (NOS) items. Results Thirteen eligible studies were identified for data synthesis and assessment. According to the result of meta-analysis, the central corneal thickness(CCT) (MD = 10.50, 95% CI: [5.01, 15.98]; P<0.05) and intraocular pressure(IOPg)(MD = -0.73, 95% CI: [-1.26, -0.19]; P<0.05) of cataract patients after phacoemulsification was significantly higher than the control groups. The values of corneal hysteresis(CH) (MD = -0.43, 95% CI: [-0.62, -0.23]; P<0.05) and corneal resistance factor(CRF) (MD = -0.49, 95% CI: [-0.64, -0.33]; P<0.05) after phacoemulsification surgery were statistically lower than the control groups. While the values of IOPcc did not show statistically different (MD = -0.13, 95% CI: [-0.67, 0.41]; P = 0.64). Conclusion Included data analysis indicated that the values of CCT, CH, CRF and IOPg showed statistical change in cataract patients after phacoemulsification surgeries compared with control groups. There is a correlation between corneal biomechanics and phacoemulsification surgeries.